New records and range extensions to the Costa Rican freshwater fish fauna, with an updated checklist - Angulo Sibaja, Arturo (2021)
The knowledge of the Costa Rican freshwater fish fauna continues to grow given the discovery of new taxa, the recognition of taxa resurrected from synonymy and the corroboration of new country records and new range extensions. Moreover, recent advances in the understanding of the phylogenetic relationships and status of many supraspecific groups have led to numerous taxonomic and nomenclatural changes. Given this, the purpose of this paper is to update the known composition, distribution and clasification of the Costa Rican freshwater fish fauna taking as reference the most recent list for the country published by Angulo et al. (2013). A total of 23 new country records (i.e., species; distributed in 17 families and 21 genera), 33 new range extensions (distributed in 20 families and 30 genera) and several nomenclatural changes are reported, illustrated and discussed here. An updated and annotated checklist of the freshwater fishes of the country (including data for a total of 283 species, 13 of which are exotic, distributed in two classes, 27 orders, 55 families and 136 genera) is also provided.